Sizing and Evaluation of Battery Energy Storage Integrated with Photovoltaic Systems. - Paulo A. V. Vieira; Felipe P. G. Silva; Bruna F. Pinheiro; Edson C. Bortoni (Department of Electrical Engineering, Institut Teknologi Nasional Malang, Indonesia, 2018)
This paper provides a review of the most common energy storage technologies and analysis of the impact of battery energy storage (BES) in a distribution network with penetration of photovoltaic. In order to reduce the intermittence impacts caused by solar panels (PV), is proposed the use an energy storage elements to stabilize the energy produced, dependent of the irradiation and temperature. Different storage technologies were considered as a function of the costs. A 100 kW PV system with integration of an energy storage was used for the simulated and analysis.